Conjectures on Cognitive Simplification in Acquisition and Divestment Decision Making - Duhaime, Irene M.; Schwenk, Charles R. (Academy of Management Review, 1985)
Acquisition and divestment decision situations generally are characterized by complexity and ambiguity. This paper proposes the idea that business decision makers may use cognitive simplifying processes in defining such ill-structured problems. A number of specific simplifying processes that may be used in acquisition and divestment are discussed. These ideas are supported by examples from recent field research and the business press. Impacts on resulting decisions are discussed; future research directions are suggested.